2012
DOI: 10.2135/cropsci2011.11.0608
|View full text |Cite
|
Sign up to set email alerts
|

Harrington Seed Destructor: A New Nonchemical Weed Control Tool for Global Grain Crops

Abstract: Global grain production is under threat from the escalating evolution of herbicide‐resistant weed populations. Worldwide, herbicide‐reliant grain crop production systems have driven the proliferation of herbicide resistant populations of major weed species. Alternatives or adjuncts to herbicides are needed for sustainable control of crop weeds in grain crops worldwide. Here we introduce and prove the ability of a new weed control tool, the Harrington Seed Destructor (HSD), to intercept and destroy weed seeds d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 26 publications
2
140
0
Order By: Relevance
“…Levels of weed seed predation have been found to be variable (Spafford et al, 2006); nonetheless, Davis (2006) thought that cropping system design for increasing weed seed predation and microbial attack may offer a cost-competitive alternative to herbicides. Weed seed management at harvest, such as burning narrow windrows (Walsh and Newman, 2007), chaff carts or using a seed destructor (Walsh et al, 2012), has similarly been shown to be very effective in reducing populations of herbicide resistant weeds in no-tillage systems. The latter approach, perhaps, provides a more reliable solution.…”
Section: Baselinementioning
confidence: 99%
“…Levels of weed seed predation have been found to be variable (Spafford et al, 2006); nonetheless, Davis (2006) thought that cropping system design for increasing weed seed predation and microbial attack may offer a cost-competitive alternative to herbicides. Weed seed management at harvest, such as burning narrow windrows (Walsh and Newman, 2007), chaff carts or using a seed destructor (Walsh et al, 2012), has similarly been shown to be very effective in reducing populations of herbicide resistant weeds in no-tillage systems. The latter approach, perhaps, provides a more reliable solution.…”
Section: Baselinementioning
confidence: 99%
“…Collection and/or physical destruction of weed seeds at harvest is an approach that could be incorporated into such systems [104]. Walsh et al [105] developed a mechanical system that destroys weed seeds which are collected during harvesting. Instead of releasing raw chaff, which contains numerous weed seeds, this system diverts the chaff into a ball mill which destroys more than 95% of weed seeds.…”
Section: Complementary Weed Management Strategiesmentioning
confidence: 99%
“…Cage mills are normally used to crush stone materials. Further research enabled scientists to destroy up to 90% of seeds of annual ryegrass (Lolium rigidum Gaudin) contained by wheat chaff during harvesting (Walsh et al 2012). HSD is a modified cage mill having a chaff-and-straw transfer system along with power source.…”
Section: Weed Seed Destructionmentioning
confidence: 99%
“…HSD is a modified cage mill having a chaff-and-straw transfer system along with power source. According to Walsh et al (2012), field studies showed that HSD offers an impressive destruction rate of above 95% for annual ryegrass, ripgut brome (Bromus diandrus Roth), wild radish (Raphanus raphsnistrum L.), and wild oat seeds (Table 2). With such impressive results, HSD is a pragmatic option for the destruction of weed seeds.…”
Section: Weed Seed Destructionmentioning
confidence: 99%